Effect of feeding heat-treated and unheated colostrum on immunoglobulin G absorption, health and performance of neonatal Holstein dairy calves - Rafiei, Mohammad; Ghoorchi, Taghi; Toghdory, Abdolhakim; Moazeni, Mostafa; Khalili, Mohsen (Acta Scientiarum. Animal Sciences, 2019)
First colostrum is an important source of nutrients and immune factors which are necessary for calves in the first weeks of life. Despite these benefits, colostrum can also represent one of the earliest potential exposures of dairy calves to infectious agents which these patogens can act directly on growth and cause diseases such as scours or septicemia. With recent increased interest in pasteurized milk feeding systems, producers have been curious to learn if there may also be benefits from feeding pasteurized colostrum. This study was realized to determine the effects of feeding heat-treated colostrum or unheated colostrum on passive transfer of immunity, immunoglobulin G (IgG) concentration, total plate count, health and performance of neonatal dairy calves. First-milking colostrum was collected from Holstein cows and frozen at -20°C to accumulate a large batch. Pooled batches of colostrum were mixed and divided equally: One half was fed unheated colostrum; whereas the other half was fed after heat treatment at 60°C for 30 min. Forty newborn male Holstein dairy calves were fed either unheated (n = 20) and heat-treated colostrum (n = 20), 10% of their birth weight. Calves received 4 L within 1 to 2h after birth and residuals was fed 6h after birth. Serum samples collected from calves and were assayed for serum total protein (STP) and IgG. Feed intake recorded weekly and body weight and skeletal growth measures recorded at d 3 and d 63 (weaning). Every day, calves clinically diagnosed either as being healthy or suffering from respiratory disease and neonatal calf diarrhea. Heat-treated colostrum resulted in lower colostrum bacterial concentration (2.01 vs. 3.96 cfu mL-1). Calves fed heat treated colostrum had greater STP in 24, 72h and 23d, IgG concentrations at 24 and 72h plus unheated colostrum. Also weaning weight and average daily gain were greater in calves feed heated colostrum. There were no differences in starter intake and feed efficiency between two groups. Calves fed heat-treated colostrum had lower fecal scores, diarrhea and pneumonia incidence. There were not differences in skeletal growth measurements except body barrel. These results shows that feeding heated colostrum can provide better growth and health in neonatal calves.